Co Gas Sensor Applications of Fe Doped Calix[4] Arene Molecules - Özbek, Cebrail; Aygün, Gülnur; Aygün, Gülnur (Izmir Institute of Technology, 2013)
Invisible and odourless carbon monoxide (CO) is one of the most toxic gas for respiratory systems. Therefore, the concentration level of carbon monoxide in the environment is extremely vital. In this thesis study, Calixarene molecules have been synthesized and the carbon monoxide selectivity and sensitivity of bare and iron doped calixarene molecules were measured by quartz crystal microbalance QCM technique and interdigitated electrodes with 3 ï m spacing. Calixarenes are promising compounds for sensing studies due to the well-designed cyclic structure, easily derivatization at both p- position of phenolic ring (upper rim) and phenolic-O (lower rim) as well as having diversely cavities which are a straightforward platform to form complex with molecules and ions. Quartz Crystal Microbalance is a powerful technique for nano scale determining the sorption properties of materials. According to Sauerbrey relation, the mass change on quartz crystal electrode cause a certain shift in the resonant frequency of vibrating crystal oscillator. This shift can be monitored using QCM method. In this study, a computer controlled QCM measurement system was developed for toxic gas detection. Iron doped calixarene based sensors were fabricated using drop-casting method on an AT-cut QCM gold electrode and interdigitated gold electrodes. The sensitivity and reproducible detection performances of prepared calixarene-iron doped calixarene thin films were measured under exposure of varying carbon monoxide for nitrogen and dry air used as desorption gas, respectively. The analysis of carbon monoxide sensitivity of iron doped calixarene is a new study for literature. This thesis study will guide future studies on this topic.
Thesis (Master)--Izmir Institute Of Technology, Physics Izmir, 2013
Includes bibliographical references (leaves: 84-89)
Text in English; Abstract: Turkish and English
x, 89 leaves
Keywords: Carbon monoxide detectors; Calixarenes; Gas detectors